Telesna podoba gibalno oviranih študentov Univerze v Ljubljani - Sedlar, Tatjana (Obzornik zdravstvene nege, 1999)
The article summarizes the diploma work at School of Health Studies and Faculty of Education at the Ljubljana University. Historically as well as today the disabled experience unequal status. The problem of physically handicapped students is serious and complex. They do not receive all the respect they deserve from the society which makes them feel inferior. By usingqualitative research, the author stresses essential factors that influence the body image of physically handicapped students and suggests some possibble solutions.
Keywords: Adult; Body image; Disabled; gibalne sposobnosti; gibanje; invalidi; motnje; Movement disorders; samopodoba; Self concept; student; Students; študenti; telesna podoba